Investigation of Bio-Gasoline Oxidation and its Influence on Fuel Supply System Components - Khoa, Nguyen Xuan; Hung, Chu Duc; Phong, Trinh Dac; Chuc, Le Huu; Vinh, Nguyen Thanh; Nghia, Nguyen Tuan (Engineering, Technology & Applied Science Research, 2025)
This study evaluated the oxidation levels of bio-gasoline fuel and its effects on non-metallic components of fuel supply systems. The experiment was conducted following the SAE J1748 standard, where components of electronic fuel injection systems were soaked in two different fuels, RON92 and E10. The soak lasted 2000 hours at 45 °C to assess the impact of fuel on weight and surface structure changes in non-metal parts. The experimental results indicate that for non-metallic parts exposed to ethanol-blended fuel, significant weight changes were observed compared to those using gasoline. Specifically, the weight of the coarse filter increased from 2.23 mg to 2.27 mg in RON92 and from 2.38 mg to 2.49 mg in E10. Similarly, the fine filter's weight increased from 6.85 mg to 6.88 mg in RON92, while in E10, it rose from 6.91 mg to 6.98 mg. The weight of the fuel level indicator tended to decrease when soaked in both RON92 and E10, with a steeper slope in E10, while the fuel float soaked in E10 decreased in weight by 0.77%, nearly two times higher than that in RON92 (0.33%).